2020
DOI: 10.1002/hpja.358
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and enablers to implementing mental well‐being programs through Australian rural football clubs—A qualitative descriptive study

Abstract: Issue addressed Suicide rates in rural Australia are almost twice as high as those in urban areas. In rural communities, football clubs are often the ‘hub’ of the community and are being explored as an avenue to deliver mental health and well‐being promotion. The aim of this study was to explore barriers and enablers for programs promoting mental health and well‐being through rural Australian football clubs. Method This qualitative descriptive study included 12 individuals of 10 rural clubs affiliated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Similarly, a study demonstrated that rural sporting clubs could serve as hubs for mental health program delivery. 34 The results of the current study add to the literature base by illustrating the diverse ways rural communities are volunteering to meet their specific and contextualised health needs, such as volunteer drivers for medical appointments, volunteer-run health and wellness centres, and voluntary informal psychosocial support groups.…”
Section: Discussionmentioning
confidence: 73%
“…Similarly, a study demonstrated that rural sporting clubs could serve as hubs for mental health program delivery. 34 The results of the current study add to the literature base by illustrating the diverse ways rural communities are volunteering to meet their specific and contextualised health needs, such as volunteer drivers for medical appointments, volunteer-run health and wellness centres, and voluntary informal psychosocial support groups.…”
Section: Discussionmentioning
confidence: 73%
“…However, the availability of an effective program is of no value if people are not participating in the opportunity, or the program is not able to be sustained [ 40 , 41 ]. Hutchesson et al identified reduced finances and a lack of volunteers as a barrier to the implementation of a program promoting mental health and well-being in rural areas of South Australia [ 42 ]. Stigma associated with mental health and lack of confidentiality in rural communities were identified as issues that may impact the help seeking behaviour of individuals [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hutchesson et al identified reduced finances and a lack of volunteers as a barrier to the implementation of a program promoting mental health and well-being in rural areas of South Australia [ 42 ]. Stigma associated with mental health and lack of confidentiality in rural communities were identified as issues that may impact the help seeking behaviour of individuals [ 42 ]. With effectiveness of the program established, future research is needed to enhance delivery through implementation planning that considers the uniqueness of the clinic and geographic settings being served as well as the people, both delivering (AEP or nurse) and participating in (patients/clients/service users) the HEAL ™ ing Mental Health program.…”
Section: Discussionmentioning
confidence: 99%
“…Players of different ages have significant differences in state anxiety. 5 There are significant differences in trait anxiety among different types of athletes. The multiple comparisons in Table 3 are state anxiety and character anxiety.…”
Section: Differences In Anxiety Levels Of Football Players Of Differe...mentioning
confidence: 99%